IMPROVING WRITING RECOUNT TEXTS ABILITY OF THE SECOND YEAR STUDENTS OF MTs HASANAH PEKANBARU THROUGH STUDENT-TEAMS ACHIEVEMENT DIVISION (STAD) - Fidel '; Eliwarti '; Masyhur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this research is to improve students’ ability in writing recount text by applying STAD as one cooperative models. This is an action research with two cycles, and each cycle consists of 4 meetings. The subject of research is a class consisted of 20 students; 6 female and 14 male students of the second year students in MTs HasanahPekanbaru. The steps of the collecting data are by administering the pre test, did action, and administering the post test at end of the cycle, and also by doing observation for the teacher’s and the students’ activities at every meeting. In each meeting, the teacher explains the material, sets the students group works, sets the individual quiz, calculates the scores, and recognizes the scores. In order to analyze the data, the writer used the T test, revealed that students’ writing ability in recount text increased after the action was administered. It could be seen that the average scores of pre test was 56.83, improved 76.42 at post test I and improved again to 79.94 at post test II. The post test II showed that the students could reach the minimum standard criterion. In addition, from the observation sheets, it showed the high students’ activities in learning process in every meeting. In brief, STAD model could improve second year students’ ability of MTs HasanahPekanbaru in writing recount text. Keywords: Student-Teams Achievement Division, STAD, Writing, Recount text, Students’ ability.